Clinicodemographic And Cutaneous Manifestation In Sars Cov-2 Infection - Mohan, Sneha; Chaudhary, Azra Ferheen; Singhal, Parul; Manjhi, Mukesh (Journal of Neonatal Surgery, 2025)
Introduction: Acute respiratory infections have emerged as a critical public health concern worldwide, with COVID-19, caused by the SARS-CoV-2 virus, being at the forefront. This virus has not only led to significant morbidity and mortality but has also been associated with a range of clinical symptoms that extend beyond the respiratory system. Aims and Objectives: The primary aim of this study is to investigate the clinic demographic profile and cutaneous manifestation of patients with confirmed SARS-CoV-2 infections. Materials and Methods: This retrospective observational study was conducted over a period of 13 months, from April 2022 to May 2023, at a tertiary care hospital. A total of 4,762 nasopharyngeal swabs were collected for RT-PCR testing, resulting in 285 confirmed cases of COVID-19. Data regarding demographic details, clinical symptoms, and any skin- related symptoms were systematically gathered through structured telephone interviews conducted with the patients or their caregivers. Results: The analysis revealed that the mean age of the 285 patients was 36.06 years, with a predominance of male patients (62.5%). The most frequently reported symptoms included fever (96.5%), myalgia (95.4%), and cough (78.6%). Notably, cutaneous manifestations were identified in 5.6 % of the patients, with the urticarial rash being the most prevalent